Optical modeling, solver, and design of macroscopic single-enantiomer carbon nanotube film and reconfigurable chiral photonic device - Fan, Jichao; Hillam, Benjamin; Guo, Cheng; Fujinami, Hiroyuki; Shiba, Koki; Xie, Haoyu; Chen, Ruiyang; Yanagi, Kazuhiro; Gao, Weilu (Carbon (New York), 2025)
The interaction of circularly polarized light with chiral matter and functional devices enables novel phenomena and applications. Recently, macroscopic solid-state single-enantiomer carbon nanotube (CNT) films have become feasible and are emerging as a chiral photonic material platform thanks to their quantum-confinement-induced optical properties and facile scalable assembly. However, optical modeling, solver, and device design tools for such materials are non-existent. Here, we prepare macroscopic single-enantiomer (6,5) and (11,-5) randomly oriented CNT films and create an optical material model based on measured experimental optical spectra. We also implement a highly-parallel graphic-processing-unit accelerated transfer matrix solver for general bi-anisotropic materials and layered structures. Further, we demonstrate reconfigurable chiral photonic devices in a heterostructure with phase change materials through machine learning-enabled efficient gradient-based inverse design and optimization. Our developed full stack of a chiral photonic material and device hardware platform and a corresponding high-performance differential-programming-enabled solver opens the door for future chiral photonic devices and applications based on single-enantiomer CNT films. [Display omitted]